Real Time Patient Monitoring System - Hiren Uthaiah M S; Jagan Babu A (International Transactions on Electrical Engineering and Computer Science, 2024)
This research introduces a comprehensive real-time patient monitoring system leveraging IoT for continuous data acquisition. The system employs Blynk, a mobile app, for real-time alerts through email and mobile notifications. Monitoring vital parameters such as temperature, humidity, and heart rate, the collected data is displayed on an LCD and stored in the cloud via the Blynk platform. An integrated buzzer ensures immediate alerts for abnormal values, enhancing the system's responsiveness. This innovative approach enhances patient care by providing instant notifications and access to crucial health metrics, contributing to proactive medical interventions.